(untitled) (Biological Sciences - PJSIR, 2002)
The microbial side-chain degradation of progesterone for the production of C-19 androgens was investigated. Thirty seven locally isolated fungal cultures were screened for their ability to degrade the side-chain of progesterone. Fusarium dimenim showed the greatest bioconversion efficiency and was selected for further studies. 50% of the substrate was converted to androstenedione after 24 hrs. 72 hrs old culture was able to prod uce maximum yields of testosterone, androstenedione and androstadienedione . The maximum conversion activities (90%) of progesterone were recorded at pH 7. The capacity of the fungu s to degrade the side-chain of progesterone was greatly dimini shed on using high concentration of progesterone . The bioconversion estimates sharply decreased by using gl ucose syrup, com steep liquor and glucose-com steep media.